1996
DOI: 10.1002/(sici)1097-0185(199608)245:4<677::aid-ar8>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Localization of proliferating cell nuclear antigen in the developing and mature rat heart cell

Abstract: Background The cardiac muscle cell ceases to divide shortly after birth; this cessation is followed by a limited period when DNA synthesis and karyokinesis occur without cytokinesis. The regulation of this process is not known. The purpose of this study is to explore the possible events that could lead to the cessation of cardiac muscle cell division. One protein requisite for DNA synthesis is proliferating cell nuclear antigen (PCNA). This protein is the auxiliary protein of DNA polymerase δ. Methods Rats of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…5,21 Western blotting of the housekeeping protein ␤-tubulin (monoclonal antibody kindly provided by Dr Zhonglin Chai, Baker HRI, Victoria, Australia) was also performed to demonstrate equal loading of the protein samples.…”
Section: Determination Of Cardiac Fibroblast Function and Mmp Activitymentioning
confidence: 99%
“…5,21 Western blotting of the housekeeping protein ␤-tubulin (monoclonal antibody kindly provided by Dr Zhonglin Chai, Baker HRI, Victoria, Australia) was also performed to demonstrate equal loading of the protein samples.…”
Section: Determination Of Cardiac Fibroblast Function and Mmp Activitymentioning
confidence: 99%
“…The PCNA protein was located at nuclei, and the cells with intense brown nuclear staining were considered positive for PCNA expression. Ten random fields per section were analyzed and the average values of the PCNA positive cell percentages were calculated [14], [15].…”
Section: Detection Of Proliferating Cell Nuclear Antigen (Pcna) Exprementioning
confidence: 99%
“…The total collagen volume fraction was determined based on the Hp concentration in the left ventricles [13]. Proliferating cell nuclear antigen (PCNA) is a 36 kDa acidic, non-histone, nuclear protein required for DNA synthesis, and can be considered as a marker of cell proliferation [14], [15]. The results showed that the Hp concentration and the nuclear expression of PCNA were significantly increased in the AC group, while treatment with EGCG 50 and 100 mg/kg for 6 weeks remarkably reduced the Hp concentration (• " Fig.…”
mentioning
confidence: 99%
“…Since CMs exit the cell cycle soon after birth, it is imperative to know the fate of these major DNA replication proteins in the adult heart cells. Although, previous studies have demonstrated down-regulation of DNA replication proteins in the adult heart [12] , [13] , [14] , however, whether the expression of RFC and Pol δ proteins are down-regulated in adult normal CMs and CFs is still elusive. In this study, we show that transcription of RFC40 gene and translation of the catalytic subunit of Pol δ protein, p125, are suppressed in the normal adult CMs.…”
Section: Introductionmentioning
confidence: 98%